MOSLEM MORAL VALUES ANALYSIS IN “HOW TO TRAIN YOUR DRAGON” MOVIE - Sumiatun1 Sumiatun1; Irmayani Irmayani; Supriyatno Supriyatno (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2017)
The literature has its roots also in the movements of expressionism and surrealism, as well as in the fiction. In this research, the researcher chooses “How to Train Your Dragon” movie. This movie is chosen to be analyzed because of the important moral value as a part of life. The purposes of this research are divided into two parts. The first purpose is to describe the Moslem moral values found in “How to Train Your Dragon” movie and the second purpose is to describe the implications of the Moslem moral values to family education. The method of this study is qualitative research. It means that it does not need statistic procedure to analyze the material. In this research, the researcher investigates the Moslem moral values in “How to Train Your Dragon” movie. Qualitative research is best suited to address a research problem which does not know the variables need to be explored. The primary data is the script of “How to Train Your Dragon” movie. The secondary data is taken from many literary books and some relevant materials to support and complete the primary data source. The result of this research is that there are some Moslem moral values in “How to Train Your Dragon” movie. From the analysis, it can be concluded that there are bravery, love, and affection, perseverance, kind and friendly, never give up, self-confidence, sorry and apologize, responsibility, honesty, and help each other.